Analisis Pengaruh Stres Kerja, Beban Kerja, dan Lingkungan Kerja terhadap Motivasi Kerja dan Kinerja Karyawan di UMKM XYZ - Farah Annisa Yasmine; Huki Chandra; Rizqa Amelia Zunaidi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
UMKM XYZ is a small-scale business that specializes in the production of krupuk. UMKM XYZ faces various challenges, including issues related to the work environment, workload, work stress, and their impact on employee motivation and performance. Thus, this study seeks to gain insights into the factors that impact the motivation and performance of employees at UMKM XYZ. By actively supporting the growth of the MSME sector in the production of krupuk. Researchers are studying the factors that impact the motivation and performance of employees at UMKM XYZ. The Partial Least Squares (PLS) method is a data analysis method that can be highly relevant depending on the characteristics of the data and the purpose of the study. The Partial Least Squares (PLS) method can be quite useful in determining the variables that have the greatest impact on explaining variability in the data. The findings of the analysis research indicated that the work environment had a notable impact on employee motivation in UMKM XYZ. The initial sample value of 0.479 indicates a significant correlation between work environment variables and work motivation. Furthermore, the T-Statistics value is 2.540 with p Values of 0.011, indicating a noteworthy finding. It is worth noting that work stress has a positive and significant influence on employee performance. The initial sample value of 0.389 indicates a significant correlation between work stress variables and employee performance. In addition, the T-Statistics value is 2.943 with p Values of 0.003.